F2-Isopostanes as novel biomarkers for type 2 diabetes: A review - Ismail, I.S.; Kaviarasan, S.; Muniandy, S.; Qvist, R. (Institute of Applied Biochemistry, 2009)
Oxidative stress (OS) has been implicated as one of the major underlying mechanisms behind many acute and chronic diseases. However, the measurement of free radicals or their end products is complicated. Isoprostanes, derived fro, the non-enzymatic peroxidation of arachidonic acid are now considered to be relieable biomarkers of oxidant stress in the human body. Isoprostanes are involved in many of the human diseases such as type 2 diabetes. In type 2 diabetes elevated levels of F2-Isoprostanes (F2-IsoPs) have been observed. The measurement of bioactive F2-IsoPs levels offers a unique noninvasive analytical tool to study the role of free radicals in physiology, oxidative stress - related diseases, and acute or chronic inflammatory conditions. Measurement of oxidative stress by various other methods lacks specificity and sensitivity. This review aims to shed light on the implementation of F2-IsoPs measurement as a gold-standard biomarker of oxidative stress in type 2 diabetes.